International Financial Statistics, January 2016. (International Financial Statistics; International Financial Statistics ;, 2016)
This January 2016 issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. IFS, Balance-of-Payments Statistics, Direction of Trade Statistics, and Government Finance Statistics are available on CD-ROM by annual subscription. The IMF normally determines the currencies that are used in transactions and operations with members. Each quarter, the IMF prepares a financial transactions plan, in which it indicates the amounts of currencies and SDRs to be used during the relevant period. The monthly printed issue of IFS reports current monthly, quarterly, and annual data, while the yearbook reports 12 observations of annual data. In IFS, exchange rates are expressed in time series of national currency units per SDR and national currency units per US dollar, or vice versa.